2021
DOI: 10.51507/j.jams.2021.14.6.207
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Electroacupuncture Pretreatment in Alleviating Myocardial Ischemia Reperfusion Injury: Interactions between the Cerebellar Fastigial Nucleus and Lateral Hypothalamic Area

Abstract: Background: Myocardial ischemia reperfusion injury (MIRI) is an important mechanism of post-myocardial infarction injury and a main cause of death in patients with ischemic heart disease. Electroacupuncture (EA) pretreatment is effective for the prevention and treatment of MIRI, but mechanisms mediating the effects of cardiovascular disease EA treatments remain unclear. Objectives: To determine whether the lateral hypothalamus (LHA) and the cerebellar fastigial nucleus (FN) are involved in the protective effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…Acupuncture represents an effective means of inducing moderate, which can activate the body’s endogenous protective mechanisms and mobilize a variety of self-feedback and regulatory mechanisms to maintain internal homeostasis [ 39 , 40 ]. Numerous studies have demonstrated that EA pretreatment has a protective effect on MIRI [ 41 43 ] and have highlighted its potential as an effective tool in the treatment of this condition [ 44 ]. This emphasizes the importance of, clarifying the mechanism of action relating to the ameliorative effects of EA pretreatment on MIRI.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture represents an effective means of inducing moderate, which can activate the body’s endogenous protective mechanisms and mobilize a variety of self-feedback and regulatory mechanisms to maintain internal homeostasis [ 39 , 40 ]. Numerous studies have demonstrated that EA pretreatment has a protective effect on MIRI [ 41 43 ] and have highlighted its potential as an effective tool in the treatment of this condition [ 44 ]. This emphasizes the importance of, clarifying the mechanism of action relating to the ameliorative effects of EA pretreatment on MIRI.…”
Section: Discussionmentioning
confidence: 99%